(untitled) (International Journal of Ayurveda and Pharma Research, 2015)
Ayurveda The science of life has been practiced in India from time immemorial and has stood test of time. This is due to the vast conceptual canvas and framework of Ayurveda. It is important to realize that, Ayurveda is not confined to medicines only, it tackles the whole subject of Life in its various ramifications. The basic fundamentals of Ayurveda are to be understood and thoroughly implemented to achieve the target of promotion of health in its true sense and complete cure from disease. According to Ayurvedic pharmacology the drug action is attributed to certain principles namely Rasa, Guna, Virya, Vipaka and Prabhava. It was observed that both the drugs as well as the living body have Panchabhutika composition in common and if the drugs are used sensibly, they can alter the body components accordingly. However if the Ayurvedic concepts are not properly understood and interpreted in globally accepted language; the tremendous efforts in research would go meaningless and futile. It is therefore strongly needed to utilize the tools derived from the advancement in technology in the new millennium for re-establishing concepts of Ayurveda in current perspectives. Although many Ayurvedic concepts described in the Samhitas seem very easy, but they are actually very difficult to understand, as the Samhitas presented everything in a concise form. There are certain concepts which need to be explored and evaluated through their practical applicability. One of such concepts is the concept of Prabhava. In a nutshell there is an urgent need to develop a process and scientific method to understand these principles. This review is an attempt to highlight the concept of Prabhava and its significance in present era.